Isolation of stress-inducible promoter Oshox24 from rice - Hội, Phạm Xuân; Nga, Trần Thị Thúy; Phương, Nguyễn Duy (Vietnam Journal of Biotechnology, 2016)
Plant improvement based on plant transformation technology has become a popular trend all over the world. The isolation and characterization of a complete set of genes/promoters associated with abiotic stress and the cross-talk among salinity, drought or temperature stresses are required for success in generating abiotic stress-resistant varieties. Recently, several studies on model plants demonstrated that the stress-responsive genes under the control of rice promoter Oshox24 were expressed specifically under stress conditions, while not affecting plant growth under normal conditions. In this study, we isolated DNA segments carrying the Oshox24 promoter from an Indica rice variety by PCR using specific primers. The Oshox24 promoter was cloned into the pGEM-T vector and fully sequenced. The nucleotide sequence of the isolated promoter Oshox24 was 1612 bp in size and had similarity of 90% in comparison to the Japonica rice promoter Oshox24 (published in GenBank as ID AP004868.3). Results of sequence analysis showed that the Indica Oshox24 promoter contains 15 stress-responsive cis-acting elements including 5 important groups ABRE, MYBRS/MYCRS, DRE, NACRS and ZFHDRS, and a TATA box located at position 1482 to 1488, suggesting that Oshox24 promoter plays an important role on regulation of abiotic stress inducible genes. The Oshox24 promoter was inserted into the expression vector pCAMBIA1300 for generating abiotic stress resistant plants in the future.